A COMPREHENSIVE OVERVIEW OF CONVERSION IN GRAMMAR (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Abstract: conversion, a linguistic process in which a word changes its part of speech without any overt morphological modification, is a widely studied phenomenon in grammar. This article provides a comprehensive overview of conversion, exploring its types, characteristics, and the underlying mechanisms that drive this linguistic process. Key topics discussed include categorical conversion, functional conversion, and zero conversion, as well as the implications of conversion for language evolution and language teaching.